A Gateway-Compatible Yeast One-Hybrid System - Deplancke, Bart; Dupuy, Denis; Vidal, Marc; Walhout, Albertha J.M. (Genome Research, 2004)
Since the advent of microarrays, vast amounts of gene expression data have been generated. However, these microarray data fail to reveal the transcription regulatory mechanisms that underlie differential gene expression, because the identity of the responsible transcription factors (TFs) often cannot be directly inferred from such data sets. Regulatory TFs activate or repress transcription of their target genes by binding to cis-regulatory elements that are frequently located in a gene's promoter. To understand the mechanisms underlying differential gene expression, it is necessary to identify physical interactions between regulatory TFs and their target genes. We developed a Gateway-compatible yeast one-hybrid (Y1H) system that enables the rapid, large-scale identification of protein-DNA interactions using both small (i.e., DNA elements of interest) and large (i.e., gene promoters) DNA fragments. We used four well-characterized Caenorhabditis elegans promoters as DNA baits to test the functionality of this Y1H system. We could detect ∼40% of previously reported TF-promoter interactions. By performing screens using two complementary libraries, we found novel potentially interacting TFs for each promoter. We recapitulated several of the Y1H-based protein-DNA interactions using luciferase reporter assays in mammalian cells. Taken together, the Gateway-compatible Y1H system will allow the high-throughput identification of protein-DNA interactions and may be a valuable tool to decipher transcription regulatory networks.